New triterpene sulfates from Vietnamese red alga Tricleocarpa fragilis and their α-glucosidase inhibitory activity. Issue 8 (15th July 2021) - Tran, Thi Van Anh; Nguyen, Van Minh; Nguyen, Thi Ai Nhung; Nguyen, Dat Huy Thanh; Tran, Duy Hien; Bui, Thi Phuong Thuy; Pham, Van Tat; Nguyen, The Han
Abstract: Three new compounds (methyl-3 β, 25-dihydroxycycloart-23-en-29-oate 3-sulfate (1 ), methyl-3 β -hydroxy-25-methoxycycloart-23-en-29-oate 3-sulfate (2 ) and 3 β -hydroxy-25-methoxycycloart-23-ene 3-sulfate (3 )) and a known one (3 β -hydroxycycloart-24-en-23-one 3-sulfate (4 )) were isolated from Vietnamese red alga Tricleocarpa fragilis . All isolated compounds 1 -4 showed potent inhibitory activity against yeast α-glucosidase with IC50 values of 16.62 ± 2.80, 36.34 ± 4.04, 30.19 ± 5.01 and 6.52 ± 0.17 µM, respectively. The docking data showed that the substitutions at C-3 and the differences in the side chain of cycloartane-skeleton could influence the interaction of molecule with enzyme, which was consistent with the experimental findings.